Aerodynamical characteristics of a reduced scale ground vehicle according to yaw angle variations. Issue 4 (25th October 2021) - Gilotte, Philippe; Mortazavi, Iraj; Colon de Carvajal, Alfonso; Edwige, Stephie; Nayeri, Christian Navid
Abstract : Purpose: The purpose of this paper is to study pressure measurement correlations, as the location of the pressure sensors should enable to capture variation of the drag force depending on the yaw angle and some geometrical modifications. Design/methodology/approach: The present aerodynamical study, performed on a reduced scale mock-up representing a sport utility vehicle, involves both numerical and experimental investigations. Experiments performed in a wind tunnel facility deal with drag and pressure measurements related to the side wind variation. The pressure sensor locations are deduced from wall streamlines computed from large eddy simulation results on the external surfaces of the mock-up. Findings: After validation of the drag coefficient (Cd) values computed with an aerodynamic balance, measurements should only imply pressure tap mounted on the vehicle to perform real driving emission (RDE) tests. Originality/value: Relation presented in this paper between pressure coefficients measured on a side sensor and the drag coefficient data must enable to better quantify the drag force contribution of a ground vehicle in RDE tests.